1992
DOI: 10.1381/096089292765560123
|View full text |Cite
|
Sign up to set email alerts
|

Revisional Surgery for Failed Gastric Restrictive Procedures for Morbid Obesity

Abstract: As part of the Adelaide Obesity Surgery Study, we have reviewed all patients who have undergone revisional surgery. Of the 31 0 trial patients, 63 (20%) had revisions 1-69 (median 32) months following their original surgery-30% of all 105 gastrogastrostomy (GG) operations, 22% of 106 gastroplasty (GP) procedures, and 9% of 99 gastric bypasses (GB). Failure was due to stomal dilatation, 11% of all trial patients (71% of GG revisions), stomal stenosis, 6% (52% of GP revisions) and staple dehiscence, 4%. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Our results are in agreement with the main points of several authors who reported good results with combined procedures [20][21][22][23] or excellent weight loss of RYGBP in spite of gastro-gastric fistula. [24][25][26] In the RYGBP-on-VBG, the nearly total passage of the meal through the non-restricted gastro-jejunal anastomosis, in spite of the open gastro-gastric outlet, can be explained by the concept of Magenstrasse: the gastrojejunostomy represents the preferential way.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with the main points of several authors who reported good results with combined procedures [20][21][22][23] or excellent weight loss of RYGBP in spite of gastro-gastric fistula. [24][25][26] In the RYGBP-on-VBG, the nearly total passage of the meal through the non-restricted gastro-jejunal anastomosis, in spite of the open gastro-gastric outlet, can be explained by the concept of Magenstrasse: the gastrojejunostomy represents the preferential way.…”
Section: Discussionsupporting
confidence: 93%
“…In the study by Hunter and colleagues, 80% of revisionary operations were not successful in patients that had failure of a primary operation due to stomal stenosis. 10 In addition, nearly 50% of the patients operated for stomal stenosis required an additional revision and 33% had recurrent stenosis; 16% of the patients ended up with a complete reversal of the original bariatric procedure. Nearly 70% of the patients in this series had multiple endoscopic procedures including balloon dilatation following their revisional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates as high as 62% have been reported with reoperative surgeries in the past. However, more recent reports demonstrate complication rates slightly lower, in the range of 10% to 40%, with the mortality rate typically 2% or less [20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%